The Pelvicachromis pulcher: A Local Aquarium Species - A.T. Ibim; G.C. Eziefule (Journal of Applied Sciences and Environmental Management)
A review was carried out on the Pelvicachromis pulcher, a local Aquarium fish that possesses a great ornamental value. The review aimed at eliciting interest in the culture of the species, as an additional aquarium fish for the development of the Ornamental fisheries industry in Nigeria. The study revealed that the Pelvicachromis pulcher, is widely distributed in southern Nigeria, western Cameroon and eastern Benin. They are a dwarf freshwater teleost fish, with males attaining a maximum length of approximately 12.5cm (4.9 in) and a maximum weight of 9.5g (0.34 oz), while the females are smaller and deeper bodied, with a maximum length of 8.1 cm (3.2 in) and a maximum weight of 9.4 g (0.33 oz). Their beautiful coloration makes them important ornamental fishes. Both sexes have a dark longitudinal stripe that runs from the caudal fin to the mouth and pink to red abdomens, the intensity of which changes during courtship and breeding. Their environmental requirements is 24-260C temperature, acidic to neutral (pH 5.6 – 6.2, and soft water (12 – 22 mg/l – 1CaCO3).They are secretive cave spawners, and exhibit vigorous parental care, but easily breed in captivity. They are omnivorous, and so easily manageable. However, its availability in the market is limited. This is as a result of certain constraints such as the absence of its Aquaculture, as very little is known about it and its economic importance where it occurs naturally, collection of fish from the wild for stocking tanks which is associated with risks in their area of occurrence.